Photo-thermal composite material, photo-thermal material composite film and preparation method
By designing WS2@C-PDA/Bi materials, using photothermal coupling technology, efficient seawater evaporation and CO2 reduction driven by solar energy are achieved, solving the problem of low efficiency of existing photothermal materials and providing an efficient resource utilization and environmental protection solution.
Patent Information
- Application Number
- CN202411821952.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-11
AI Technical Summary
When existing photothermal materials use solar energy for seawater desalination and carbon dioxide reduction, they are less efficient and difficult to take into account both photothermal conversion and carbon dioxide reduction.
A photothermal composite material was designed, using tungsten disulfide (WS2) as the core, covering the carbon layer with the outside, and loading bismuth elements on the surface of the carbon layer to form WS2@C-PDA/Bi material. This material uses photothermal coupling technology to achieve efficient seawater evaporation and CO2 reduction driven by solar energy.
The photothermal conversion efficiency and catalytic activity are significantly improved, and efficient seawater evaporation and carbon dioxide reduction are achieved, providing a new solution to the problems of freshwater shortage and excessive carbon dioxide emissions.
Smart Images

Figure CN119660864A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photothermal materials, and in particular relates to a photothermal composite material, a photothermal material composite film and a preparation method thereof. Background Art
[0002] With the rapid development of human society, the demand for energy and fresh water resources has increased dramatically, resulting in an increasing shortage of fresh water resources. At the same time, human activities not only consume energy and fresh water resources, but also emit a large amount of CO2 into the atmosphere, causing the greenhouse effect to continue to damage the earth's environment. To meet this challenge, people have carried out a lot of research on photothermal coupled catalytic systems, aiming to efficiently utilize solar energy and achieve synergistic efficiency of seawater desalination and green energy conversion.
[0003] Photothermal nanomaterials have shown broad application prospects in the fields of solar desalination, carbon dioxide reduction, hydrogen production, etc. These light-absorbing materials can efficiently absorb light energy and convert photons into heat energy, thereby significantly improving evaporation performance. In addition, the electron-hole pairs generated by photothermal nanomaterials under light can effectively enhance the activity of photocatalysts and promote the conversion of solar energy into chemical energy.
[0004] In order to effectively utilize photothermal materials, the current strategy is mainly to directly confine the heat energy converted from solar energy between interfaces. A common method is to float photothermal materials on the surface of water bodies. After photothermal materials convert solar energy into heat energy, they are confined to the surface water layer instead of heating the entire water body. This allows the heat energy to be directly and effectively absorbed and utilized by the surface water layer, thereby improving the overall photothermal conversion efficiency.
[0005] Through further research, the present invention aims to provide a photothermal material that can simultaneously take into account photothermal conversion and carbon dioxide reduction.
[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0007] The object of the present invention is to provide a photothermal composite material, a photothermal material composite film and a preparation method, which realizes solar-driven efficient seawater evaporation and CO2 reduction through photothermal coupling technology.
[0008] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0009] A photothermal composite material, wherein the photothermal composite material takes tungsten disulfide as a core, the surface of the core is coated with a carbon layer, and the surface of the carbon layer is loaded with bismuth elements.
[0010] In one or more embodiments of the present invention, the carbon layer has a thickness of 16-150 nm.
[0011] In one or more embodiments of the present invention, tungsten disulfide coated with a carbon layer is used as a carrier, and the loading amount of the bismuth element is ≤100%.
[0012] In one or more embodiments of the present invention, the particle size of the tungsten disulfide is 1-5 μm.
[0013] Another specific embodiment of the present invention provides a technical solution as follows:
[0014] A method for preparing a photothermal composite material comprises the following steps:
[0015] Coating a carbon layer on the surface of tungsten disulfide to obtain a carbon-coated tungsten disulfide material;
[0016] The carbon-coated tungsten disulfide material is dispersed in a bismuth source solution, a reducing agent is added for reduction, and then centrifuged, and the precipitate is collected and dried to obtain a photothermal composite material.
[0017] In one or more embodiments of the present invention, the mass ratio of the carbon-coated tungsten disulfide material to the bismuth source, calculated as bismuth element, is 100:(1-100).
[0018] In one or more embodiments of the present invention, the preparation of the carbon-coated tungsten disulfide material is as follows:
[0019] Disperse tungsten disulfide in a solvent, add dopamine hydrochloride solution according to the mass ratio of tungsten disulfide to dopamine hydrochloride of 1: (0.5-2), centrifuge after reaction, collect the precipitate, freeze-dry the precipitate, and obtain polydopamine-coated tungsten disulfide material;
[0020] The polydopamine-coated tungsten disulfide material is calcined at 600-800° C. for 0.5-3 h to obtain a carbon-coated tungsten disulfide material.
[0021] Another specific embodiment of the present invention provides a technical solution as follows:
[0022] A photothermal material composite film comprises a substrate layer and an active layer arranged on the substrate layer, wherein the active layer is formed by the photothermal composite material or the photothermal composite material prepared by the preparation method of the photothermal composite material.
[0023] In one or more embodiments of the present invention, the base layer is a polyvinylidene fluoride film, a mixed cellulose ester film or a polypropylene film.
[0024] Another specific embodiment of the present invention provides a technical solution as follows:
[0025] A method for preparing a photothermal material composite film comprises the following steps:
[0026] Dispersing the photothermal composite material in deionized water to obtain a dispersion;
[0027] The dispersion is poured into a suction filtration device equipped with a substrate layer, and then suction filtered, and then dried to obtain a photothermal material composite membrane.
[0028] Compared with the prior art, the present invention innovatively designs the WS2@C-PDA / Bi material, which is a core-shell structure using a tungsten disulfide (WS2) core, an external carbon layer, and metal bismuth loaded on the carbon layer. The WS2 core provides excellent photothermal conversion performance, and the external carbon layer increases the light absorption area and photothermal conversion efficiency while maintaining the generated heat and reducing radiation loss. The loading of metal bismuth further enhances the photocatalytic performance and significantly promotes the carbon dioxide reduction reaction.
[0029] In addition, the present invention designs a photothermal material composite membrane, the active layer is composed of the prepared WS2@C-PDA / Bi material, and the lower part is a polyvinylidene fluoride (PVDF) membrane. The photothermal material composite membrane is assembled into an interface system, which can not only effectively convert light energy into thermal energy, thereby realizing seawater evaporation and desalination, but also use photocatalysis to reduce carbon dioxide to carbon monoxide and methane.
[0030] The multifunctional membrane structure of the photothermal material composite membrane combines the dual functions of photothermal and photocatalysis, and the PVDF membrane provides good mechanical strength and chemical stability, ensuring the long-term stable operation of the system. This membrane shows significant advantages in the process of solar-driven freshwater collection and carbon dioxide reduction, which not only improves the overall efficiency of the system, but also provides an important reference for future energy capture and resource utilization technologies. This innovation not only has significant economic and environmental benefits, but also provides a new solution to the problems of freshwater shortage and excessive carbon dioxide emissions. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 A schematic structural diagram of a photothermal material composite film in one embodiment of the present invention;
[0033] Figure 2 : This is a projection electron microscope image of WS2@C-PDA particles in Example 1 of the present invention;
[0034] Figure 3 The original WS2 material, the material after calcination with PDA and the material after Bi loading in Example 1 of the present invention;
[0035] Figure 4 Schematic diagram of the 3D structure of WS2@C-PDA / Bi material in Example 1 of the present invention;
[0036] Figure 5 Element distribution diagram of WS2@C-PDA / Bi material in Example 1 of the present invention;
[0037] Figure 6 is a SEM image of the raw material WS2 in Example 1 of the present invention;
[0038] Figure 7 This is the SEM image of the WS2@C-PDA material in Example 1 of the present invention;
[0039] Figure 8 This is the SEM image of the WS2@C-PDA / Bi material in Example 1 of the present invention;
[0040] Fig. 9 XRD images of raw material WS2, WS2@C-PDA material, and WS2@C-PDA / Bi material in Example 1 of the present invention;
[0041] Fig.10 It is a schematic diagram of the structure of the interface floating system in the evaporation test;
[0042] Fig.11 (a) is a comparison chart of the evaporation rates in Examples 1-7 and Comparative Example 1;
[0043] Fig.11 (b) is the evaporation rate of WS2@C-PDA / Bi@PVDF film in Example 5;
[0044] Fig.12 A comparison chart of carbon dioxide reduction in Examples 1-7 and Comparative Example 1;
[0045] Fig.13 This is the absorbance diagram of the raw material WS2 and WS2@C-PDA / Bi material in Example 5 of the present invention;
[0046] Fig.14 The PC response diagram of WS2@C-PDA / Bi material in Examples 1-7 of the present invention and Comparative Example 1;
[0047] Fig.15 Schematic diagram of seawater evaporation and CO2 reduction using the WS2@C-PDA / Bi material of the present invention. DETAILED DESCRIPTION
[0048] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0049] A specific embodiment of the present invention provides a photothermal composite material, which uses tungsten disulfide as a core, the surface of the core is coated with a carbon layer, and the surface of the carbon layer is loaded with bismuth elements.
[0050] Furthermore, the bismuth element is selected from metallic bismuth. Preferably, the bismuth element is nano-metal bismuth particles, and the particle size of the nano-metal bismuth particles is 20 to 60 nm.
[0051] Specifically, tungsten disulfide (WS2) has excellent photothermal properties and can absorb light energy and convert it into heat energy. Metallic bismuth has high catalytic activity and can effectively promote the reaction of carbon dioxide. The material prepared by compounding tungsten disulfide and bismuth has good chemical and thermal stability and can maintain stable operation for a long time at high temperature. In addition, the use of a carbon layer to isolate the internal tungsten disulfide particles from the metal bismuth can effectively promote the separation of photogenerated carriers and further enhance the catalytic activity and photothermal effect of the photothermal composite material. Moreover, wrapping a carbon layer on the surface of tungsten disulfide can improve the photothermal conversion efficiency of tungsten disulfide because the carbon layer provides a larger light absorption area and better thermal conductivity. In addition, the presence of the carbon layer can effectively maintain the heat generated by the internal tungsten disulfide particles, reduce heat radiation loss, increase the surface area of the photothermal composite material, expand the contact with the catalyzed substance, and improve the catalytic efficiency.
[0052] Furthermore, the particle size of tungsten disulfide is 1-5 μm, the thickness of the carbon layer is 16-150 nm, and the tungsten disulfide coated with the carbon layer is used as a carrier, and the loading amount of the bismuth element is ≤100%.
[0053] Specifically, by controlling the thickness of the carbon layer, it is helpful to improve the photothermal conversion effect of the photothermal composite material, and the evaporation of seawater can be increased. At the same time, controlling the particle size of tungsten disulfide and the loading amount of bismuth can further ensure that the photothermal composite material has excellent photothermal conversion effect.
[0054] Another specific embodiment of the present invention provides a method for preparing a photothermal composite material, comprising steps 1-2.
[0055] Step 1: coating a carbon layer on the surface of tungsten disulfide to obtain a carbon-coated tungsten disulfide material.
[0056] Specifically, tungsten disulfide powder is added to a sodium bicarbonate solution, and stirred at 400-1000 rpm for 30-60 minutes by magnetic stirring to make it uniformly dispersed. In addition, dopamine hydrochloride is taken, and the mass ratio of tungsten disulfide powder to dopamine hydrochloride is 1: (0.5-2), and the preferred ratio is 1: 1. Dopamine hydrochloride is ultrasonically dissolved in a sodium bicarbonate solution, and then the obtained dopamine hydrochloride solution is added to the tungsten disulfide dispersion, stirred at 4000-10000 rpm for 6-24 hours, and then centrifuged at 4000-10000 rpm for 3-5 minutes. The obtained precipitate is first washed once with deionized water and anhydrous ethanol, and then the washed precipitate is freeze-dried overnight using a freeze dryer, and the fully dried powder sample is collected to obtain a polydopamine-coated tungsten disulfide material. The sodium bicarbonate solution provides an alkaline environment to polymerize dopamine hydrochloride to form polydopamine. In addition to sodium bicarbonate, other substances that can provide an alkaline environment can also be selected.
[0057] Then the polydopamine coated tungsten disulfide material is placed in a tube furnace, the temperature is raised to 600-800° C. at a heating rate of 2-5° C. / min, and calcined for 0.5-3 h to obtain a carbon coated tungsten disulfide material.
[0058] Furthermore, polydopamine (PDA) has excellent coating ability when used as a coating material. PDA can form a uniform coating on the surface of tungsten disulfide, and the polyphenol groups in its molecules can be tightly bound to tungsten disulfide through covalent and non-covalent bonds, ensuring the uniformity and integrity of the coating process. In addition, PDA has good biocompatibility and is very suitable for use in biomedical and environmental applications without causing adverse reactions or pollution. The functional groups on the surface of PDA (such as amino and hydroxyl groups) are easy to further modify and functionalize, thereby giving the material more functional properties. During the calcination process, PDA can be converted into a carbon layer to form a stable carbon coating structure, which not only enhances the photothermal performance, but also provides more active sites and improves the catalytic efficiency.
[0059] Step 2: disperse the carbon-coated tungsten disulfide material in a bismuth source solution, add a reducing agent for reduction, and then centrifuge to collect and dry the precipitate to obtain a photothermal composite material.
[0060] Furthermore, the bismuth source is a water-soluble bismuth salt, preferably, the bismuth source is bismuth nitrate hydrate, and more preferably, the bismuth source is bismuth nitrate pentahydrate.
[0061] Specifically, the mass ratio of the carbon-coated tungsten disulfide material to the bismuth source is 100: (1-100) in terms of bismuth element. Taking bismuth nitrate pentahydrate as an example, according to the mass ratio of the carbon-coated tungsten disulfide material to bismuth nitrate pentahydrate of 100: (2.32-232), the bismuth nitrate pentahydrate is dissolved in water, and then the carbon-coated tungsten disulfide material is dispersed in the bismuth nitrate pentahydrate aqueous solution, and then slowly dripped with a concentration of 0.4M sodium borohydride aqueous solution under stirring conditions. The amount of sodium borohydride aqueous solution can be adjusted according to the mass of bismuth nitrate pentahydrate, and the maximum amount can be 62.5ml. After the dripping is completed, it is continuously stirred at 400-1000rpm for 30-60min, and then centrifuged at 4000-10000rpm, and the precipitate is collected and dried to obtain a photothermal composite material. Sodium borohydride is used as a reducing agent to react with bismuth nitrate pentahydrate to generate bismuth element. In addition to sodium borohydride, other available reducing agents can also be selected.
[0062] Another specific embodiment of the present invention provides a photothermal material composite film, such as Figure 1 As shown, it includes a base layer and an active layer arranged on the base layer, and the active layer is formed by the above-mentioned photothermal composite material or the photothermal composite material prepared by the above-mentioned preparation method of the photothermal composite material.
[0063] Specifically, the substrate layer can be selected from polyvinylidene fluoride membrane (PVDF membrane), mixed cellulose ester membrane or polypropylene membrane, preferably polyvinylidene fluoride membrane. PVDF membrane has excellent mechanical strength and durability, can maintain integrity and stability under various harsh conditions, and provide reliable structural support; PVDF membrane has good tolerance to many chemicals, can resist corrosion by acids, alkalis and organic solvents, and ensure long-term use in complex chemical environments; PVDF membrane has high thermal stability, can be used in high temperature environments without degradation, and is suitable for applications with high temperature operations; PVDF membrane can also maintain performance in water environments, and is particularly suitable for water treatment applications such as seawater desalination.
[0064] Another specific embodiment of the present invention provides a method for preparing a photothermal material composite film, comprising the following steps:
[0065] Dispersing the photothermal composite material in deionized water to obtain a dispersion;
[0066] The dispersion is poured into a suction filtration device equipped with a substrate layer, and then suction filtered, and then dried to obtain a photothermal material composite membrane.
[0067] The present invention is further described in detail below in conjunction with specific embodiments.
[0068] Example 1
[0069] Take 1g of WS2 with a particle size of 2μm, add it to 80ml of 0.1M NaHCO3 solution, stir it magnetically at 400rpm for 30min to make it evenly dispersed, and obtain solution A. Weigh 1g of dopamine hydrochloride, dissolve it in 20ml of 0.1M NaHCO3 solution, and ultrasonicate it for 30min to obtain solution B. Slowly add solution B to solution A to obtain solution C, and stir it at 400rpm for 24h, then centrifuge it at 8000rpm for 5min, and collect the precipitate. Wash the precipitate once with deionized water and anhydrous ethanol respectively, and finally freeze-dry the washed precipitate overnight using a vacuum dryer, collect the fully dried powder sample, and obtain WS2@PDA powder.
[0070] The WS2@PDA powder was placed in a tube furnace, heated to 700°C at a heating rate of 3°C / min, and calcined for 3 h to obtain the WS2@C-PDA material. Figure 2 It can be seen that there is a carbon layer on the surface of WS2 located in the core.
[0071] Take 0.012g of bismuth nitrate pentahydrate, dissolve it in 100ml of deionized water, take another 100mg of WS2@C-PDA material and add it to the bismuth nitrate pentahydrate solution, then slowly add 3.125ml of 0.4M sodium borohydride aqueous solution under stirring, and continue stirring for 30min after the addition is complete. Then centrifuge the solution at 8000rpm, collect the precipitate and dry it at 60℃ to obtain WS2@C-PDA / Bi material, that is, photothermal composite material. The loading amount of bismuth element on WS2@C-PDA material is 5%, and the loading amount is calculated as (mass of bismuth element / mass of WS2@C-PDA material)*100%.
[0072] Schematic diagram of the 3D structure of WS2@C-PDA / Bi material Figure 4 As shown, the photothermal reaction core is WS2, and its surface is coated with a carbon layer, and the surface of the carbon layer is loaded with nano-metal particles, namely metal bismuth. Figure 5 From the element distribution diagram, it can be found that there are carbon and bismuth elements on the surface of WS2; Figure 6-8 From the morphology diagram, we can see that after carbon coating, the surface morphology of the original WS2 changes from irregular to more rounded, and irregular sticks appear on the surface of WS2@C-PDA / Bi nanoparticles, confirming the loading of metal Bi. Fig. 9 In the XRD spectrum, obvious Bi element characteristic peaks appeared at 22.5°, 27.5° and 38° (PDF 00-005-0519), which also confirmed that Bi element had been successfully loaded.
[0073] 10 mg of WS2@C-PDA / Bi material was placed in a 200 ml beaker, 150 ml of deionized water was added, magnetic stirring was performed for 1 h, ultrasonication was performed for 20 min, and repeated three times to make a uniform solution. Then, the solution was poured into a filtration device with a PVDF membrane with a diameter of 50 mm and a pore size of 0.45 μm by vacuum filtration. After the filtration was completed, the WS2@C-PDA / Bi@PVDF membrane was taken out and dried naturally at room temperature to obtain a photothermal composite membrane, which was recorded as WCB-5.
[0074] Embodiment 2-7
[0075] The operation of Examples 2-7 is the same as that of Example 1, except that the amounts of bismuth nitrate pentahydrate and sodium borohydride aqueous solution are different, as shown in Table 1.
[0076] Table 1 Amount of raw materials used in Examples 1-7
[0077]
[0078] Comparative Example 1
[0079] Take 1g of WS2 with a particle size of 2μm, add it to 80ml of 0.1M NaHCO3 solution, stir it magnetically at 400rpm for 30min to make it evenly dispersed, and obtain solution A. Weigh 1g of dopamine hydrochloride, dissolve it in 20ml of 0.1M NaHCO3 solution, and ultrasonicate it for 30min to obtain solution B. Slowly add solution B to solution A to obtain solution C, and stir it at 400rpm for 24h, then centrifuge it at 8000rpm for 5min, and collect the precipitate. Wash the precipitate once with deionized water and anhydrous ethanol respectively, and finally freeze-dry the washed precipitate overnight using a vacuum dryer, collect the fully dried powder sample, and obtain WS2@PDA powder.
[0080] The WS2@PDA powder was placed in a tube furnace, heated to 700°C at a heating rate of 3°C / min, and calcined for 3 h to obtain the WS2@C-PDA material.
[0081] 10 mg of WS2@C-PDA material was placed in a 200 ml beaker, 150 ml of deionized water was added, magnetic stirring was performed for 1 h, ultrasonication was performed for 20 min, and repeated three times to make a uniform solution. Then, the solution was poured into a filtration device with a PVDF membrane with a diameter of 50 mm and a pore size of 0.45 μm by vacuum filtration. After the filtration was completed, it was taken out and dried naturally at room temperature, that is, the photothermal material composite membrane, recorded as WCB-0.
[0082] The following tests were performed on the photothermal material composite films in each embodiment and comparative example:
[0083] (1) Evaporation test: Fig.10 As shown, the photothermal material composite film is placed on absorbent cotton, which is bonded to polyethylene foam to form an interfacial floating system. The absorbent cotton wraps the upper part of the foam, and the foam provides buoyancy. The absorbent cotton absorbs water to the bottom of the photothermal material composite film for evaporation. The system is placed in a container filled with seawater, and the container is placed on a balance. The balance is connected to a computer and records the change in weight after evaporation of water through the computer. The balance is placed under the solar simulator, and the solar simulator is used to simulate sunlight irradiation on the photothermal material composite film. The irradiation intensity is set to 1000w / m 2 .
[0084] (2) Carbon dioxide reduction test: 50 mg of WS2@C-PDA / Bi material was dispersed in 100 mL of distilled water without any sacrificial agent. The reaction solution was kept at 5 °C by a circulating cooling water system, and then evacuated several times to completely remove the air. A 300 W Xe lamp was used as the light source. The generated gas was detected by a TCD equipped with a The molecular sieve column is measured by gas chromatography (using argon as carrier gas). In addition, the gas chromatograph is used to detect the peak signals of CH4, CO, etc., and then the rate of CO2 reduction to CH4 and CO is calculated as follows:
[0085]
[0086] Fig.11 In the figure, the Bi concentration (%) on the abscissa refers to the loading amount of bismuth on the WS2@C-PDA material. Fig.11 It can be seen that in the evaporation test, the seawater evaporation efficiency of the photothermal material composite film in Comparative Example 1 is the lowest. The photothermal material composite films loaded with bismuth in the embodiments of the present invention can effectively convert light energy into heat to achieve photothermal seawater evaporation. Among them, the evaporation rate of the WCB-40 film is the largest. At 30 minutes, the seawater evaporation rate of the WCB-40 film reaches a stable level, and the average evaporation rate after 30 minutes can reach about 1.12 kg / m 2 / h.
[0087] Fig.12 In the figure, the Bi concentration (%) on the abscissa refers to the loading amount of bismuth on the WS2@C-PDA material. Fig.12 It can be seen that in the carbon dioxide reduction test, compared with comparative example 1, the photothermal composite material loaded with metal bismuth can effectively reduce carbon dioxide. When the loading amount of metal bismuth is 40%, the CO yield of WS2@C-PDA / Bi@PVDF membrane reaches 9.18mmol / g, which is the best performance. Fig.13 It can be seen that in the solar light band of 200 to 2500 nm, the absorbance of the WCB-40 sample is as high as 91%. Fig.14 In the table, 0 represents WCB-0, 10 represents WCB-10, 40 represents WCB-40, 50 represents WCB-50, and 100 represents WCB-100. Fig.14 It can be seen that in the photoelectrochemical response results, the light response intensity of the WCB-40 sample is the strongest, indicating that the WCB-40 sample has a higher rapid transfer and separation of light-induced charges, which is more conducive to CO2 reduction.
[0088] In summary, if Fig.15 As shown in the figure, the present invention realizes solar-driven seawater evaporation and CO2 reduction through photothermal coupling technology, providing a new solution to alleviate freshwater shortage and environmental problems. The photothermal material composite film in the present invention is used as the photothermal layer, foam is used as the thermal insulation layer, and absorbent cotton is used as the water transport layer to form an interfacial photothermal seawater evaporation structure. In specific applications, photothermal seawater evaporation and desalination can be achieved, and its evaporation and desalination efficiency reaches 1.12kg / m 2 / h. While generating photothermal energy, the photothermal layer is excited by light and photocatalyzed, with the yield of CO2 reduced to CO reaching up to 9.18mmol / g.
[0089] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0090] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A photothermal composite material, characterized in that: The photothermal composite material uses tungsten disulfide as a core, the surface of the core is coated with a carbon layer, and the surface of the carbon layer is loaded with bismuth elements.
2. The photothermal composite material according to claim 1, characterized in that: The carbon layer has a thickness of 16 to 150 nm.
3. The photothermal composite material according to claim 1, characterized in that: Tungsten disulfide coated with a carbon layer is used as a carrier, and the loading amount of the bismuth element is ≤100%.
4. The photothermal composite material according to claim 1, characterized in that: The particle size of the tungsten disulfide is 1 to 5 μm.
5. A method for preparing a photothermal composite material, characterized in that: The following steps are involved: Coating a carbon layer on the surface of tungsten disulfide to obtain a carbon-coated tungsten disulfide material; The carbon-coated tungsten disulfide material is dispersed in a bismuth source solution, a reducing agent is added for reduction, and then centrifuged, and the precipitate is collected and dried to obtain a photothermal composite material.
6. The method for preparing the photothermal composite material according to claim 5, characterized in that: The mass ratio of the carbon-coated tungsten disulfide material to the bismuth source, calculated as bismuth element, is 100:(1-100).
7. The method for preparing the photothermal composite material according to claim 5, characterized in that: The preparation of carbon-coated tungsten disulfide material is as follows: Disperse tungsten disulfide in a solvent, add dopamine hydrochloride solution according to the mass ratio of tungsten disulfide to dopamine hydrochloride of 1: (0.5-2), centrifuge after reaction, collect the precipitate, freeze-dry the precipitate, and obtain polydopamine-coated tungsten disulfide material; The polydopamine-coated tungsten disulfide material is calcined at 600-800° C. for 0.5-3 h to obtain a carbon-coated tungsten disulfide material.
8. A photothermal material composite film, characterized in that: The invention comprises a base layer and an active layer arranged on the base layer, wherein the active layer is formed by the photothermal composite material according to any one of claims 1 to 4 or by the photothermal composite material prepared by the preparation method of the photothermal composite material according to any one of claims 5 to 7.
9. The photothermal material composite film according to claim 8, characterized in that: The base layer is a polyvinylidene fluoride film, a mixed cellulose ester film or a polypropylene film.
10. A method for preparing a photothermal material composite film, characterized in that: The steps include: Dispersing the photothermal composite material in deionized water to obtain a dispersion; the photothermal composite material is the photothermal composite material according to any one of claims 1 to 4 or the photothermal composite material prepared by the method for preparing the photothermal composite material according to any one of claims 5 to 7; The dispersion is poured into a suction filtration device equipped with a substrate layer, and then suction filtered, and then dried to obtain a photothermal material composite membrane.
Citation Information
Patent Citations
Preparation method of WS2 nano-material with macroporous network structure
CN108039289A
Preparation method of carbon-coated iron, cobalt, nickel nitrogen hybrid material by high-efficiency photothermal reduction of CO2
CN109289893A
Copper-decorated porous graphite carbon shell coated iron catalyst as well as preparation method and application thereof
CN118341426A
PHOTOCATALYTIC REDUCTION PROCESS FOR CARBON DIOXIDE USING A PHOTOCATALYST BASED ON MOLYBDENNE SULFIDE OR TUNGSTEN SULFIDE SUPPORT
FR3073429A1